Economic efficiency of human urine as fertilizer in the production of NERICA 4 rice in the Sudano-Sahelian zone of Mali - Coulibaly, Ousmane; Sissoko, Sory; Coulibaly, Alou; Maiga, Yacouba; Dicko, Mohamed; G Dembele, Sidiki; S Maiga, Mohamed (International Journal of Environment, Agriculture and Biotechnology, 2024)
In West Africa, and particularly in Mali, rice is the staple food of the population. However, its production is faced with various constraints, including soils poor on the one hand and difficult access to inputs on the other. Indeed, waste, especially excreta, contains nutrients that are essential for crop development. It is within this framework that this study was conducted to determine the human urine effect on the production of NERICA 4 rice in the Sudano-Sahelian zone. Different urine doses in combination or not with organic fertilizer were put in competition through an experimental design in Ficher Block with eight repetitions. The results after variance analysis showed statistical differences between treatments. The yield increase was most marked with the 111 kg N/ha urine + 5 t organique fumure (T7), which provided the highest rice yield with 1623 kg/ha compared to the mineral fertilizer control (T9) with 1550 kg/ha.The analysis of economic profitability shows that the dose 111kg N/ha urine alone with a ratio of 3.32 is better than the other doses of fertilizers compared to the FAO standard (RVC > 2).